ANALISIS KREATIVITAS MAHASISWA DALAM PENYUSUNAN PETA KONSEP BERBENTUK E-MIND MAP BERDASARKAN KAJIAN NEUROSAINS - Vica Dian Aprelia Resti (Jurnal Pendidikan Biologi, 2015)
The learning process are many stimulus interaction have to increase motivation in learning activities. Beginning with the learning experience from students that involve brain mechanism to processing of information into long-term memory structures. Student as subjects of learning have any problems, such as their creativity level is low to make solutions idea about some problems. Based on the problems about the low level creativity of student, the research to analyze the creativity level with making mind map and describe the role of neurosains about them. The subjects of all students in department of science education, there are 36 students. Based on result the students get 5 score for display aspect, 3 score for colors and images, 3 score for keywords, 3 score relationships about main branch with other branches, and 3 score for exploration aspect. Based on average score, the lowest score is 64 and highest score is 80. The students get score in range of 64-69 for 5 students, 70-79 for 30 students, and 80 for 1 student.Keywords: mind map, creativity, neurosains